2000
DOI: 10.1128/iai.68.3.1655-1663.2000
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Synthetic Antiendotoxin Peptides on Lipopolysaccharide (LPS) Recognition and LPS-Induced Proinflammatory Cytokine Responses by Cells Expressing Membrane-Bound CD14

Abstract: Lipopolysaccharides (LPS), or endotoxins, are major structural and functional components of the outer membrane of gram-negative bacteria (24). These complex macromolecules exhibit a variety of toxic and proinflammatory activities that are associated with the lipid A moiety and are causally related to the pathogenesis of gram-negative sepsis and septic shock (17, 18).Many of the local and systemic pathophysiologic phenomena produced by LPS in the exposed host result from the ability of LPS to activate host infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…In this study, to develop cathelicidin-derived antimicrobial peptides with improved LPS-neutralizing activities, we utilized the 18-mer peptide (K 15 -V 32 ) of human cathelicidin hCAP18/ LL-37 as a template and evaluated the activities of its peptide derivatives. By replacement of E 16 and K 25 with two L residues, the hydrophobicity of the peptide was increased and the hydrophobic sector in the helix was extended ( Fig. 1 and 11; compare 18-mer K 15 -V 32 with 18-mer LL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, to develop cathelicidin-derived antimicrobial peptides with improved LPS-neutralizing activities, we utilized the 18-mer peptide (K 15 -V 32 ) of human cathelicidin hCAP18/ LL-37 as a template and evaluated the activities of its peptide derivatives. By replacement of E 16 and K 25 with two L residues, the hydrophobicity of the peptide was increased and the hydrophobic sector in the helix was extended ( Fig. 1 and 11; compare 18-mer K 15 -V 32 with 18-mer LL).…”
Section: Discussionmentioning
confidence: 99%
“…For prevention of bacterial infections and their related symptoms (e.g., gram-negative bacterial septic shock), much attention has been focused on the low-molecular-weight cationic antimicrobial peptides that possess both antibacterial and LPS-neutralizing activities (5,14,16,17,20,28,33,40,49). Previously, it was demonstrated that in addition to exhibiting potent antibacterial activity against gram-positive and gramnegative bacteria (34), hCAP18/LL-37 could bind to the lipid-A moiety of LPS and inhibit the interaction of LPS with LBP, which transports LPS to CD14 ϩ cells, thereby suppressing the binding of LPS to CD14 ϩ cells (33) and possibly attenuating Toll-like receptor-mediated CD14 ϩ cell activation (2,4,19,48).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Iwagaki et al (40) investigated the binding of LPS to CD14 ϩ cells using synthetic antiendotoxin peptides that were designed to mimic the structures of polymyxin B, which inhibits the biological activities of LPS through its high affinity binding to the lipid A moiety of LPS. In addition, Dankesreiter et al (41) synthesized the hybrid peptides containing LPS-binding domains from Limulus anti-LPS factor and LBP and examined their effects on the interaction of LPS with CD14 ϩ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides based on BPI (172), LBP (78), CAP18 (264), CAP37 (50), lactoferrin (615), SAP (87), Limulus anti-LPS factor (LAL) (451), bee melittin (479,480), silk moth cecropin (479,480), and the antibiotic peptide polymyxin B (238) have been constructed and tested on bactericidal, LPS-or LTA-binding, and neutralizing potency in vitro and in vivo. The results with these peptides with respect to binding, neutralization, and bactericidal activity are promising, but it was shown that the spatial organization of the positive and hydrophobic moieties largely determines the binding affinity of the peptides for the bacterial compounds (238,354). Further investigations are needed to determine an optimal structure and may lead to the construction of a potent and highly specific peptide-based antibiotic and LPS-and LTA-neutralizing peptide.…”
Section: Development Of Bactericidal and Lipopolysaccharide-neutralizmentioning
confidence: 99%